The Management and Associated Costs of Rearing Heifers on UK Dairy Farms from Weaning to Conception - Boulton AC; Rushton J; Wathes DC (Scientific Research Publishing)
Dairy heifers only start to produce a return on investment at first calving. The length of the nonproductive rearing period is largely governed by farmer decisions on plane of nutrition and reproduction management. Primary data were collected from 101 dairy farms and a cost analysis workbook developed to calculate individual inputs in each of three periods to determine which management decisions and farm factors have the greatest influence on the total costs associated with rearing. This paper covers weaning until conception. Heifers were weaned at 62 d (range 42 - 112 d) and conceived by 509 d (range 365 - 700 d) giving an average weaning to conception period of 447 ± 60 d (range 253 to 630 d). The mean daily cost of rearing during this period was £1.65 (range £0.75 to £2.97 on different farms) giving a mean total cost of £745.94 per heifer (range £295.32 to £1745.85). This large variation was mostly due to the duration, which was mainly determined by age at first breeding (mean 476 days, range 365 - 700 d). The main contributors to total costs were feed (35.6%), labour (24.7%) and bedding (8.9%). The variables most strongly associated with the total costs were age at conception, calving pattern and breed. A multivariable model predicted an increase in mean cost of £2.26 for each extra day in age at conception. The total cost was highest in herds with all year round calving, intermediate in multi-block and lowest in spring and autumn calving herds, with Friesian x and Jersey herds having the lowest cost of rearing.
Keywords: Heifer; Cost Analysis; Sexed Semen